In vitro influence of nutrient deprivation and papaverine exposure in MCF-7 and MDA-MB-231 breast cancer cell lines - Visagie, M.H. (Michelle Helen) (University of Pretoria, 2025)
Dissertation (MSc (Human Physiology))--University of Pretoria, 2025.